53.7k views
3 votes
HURRY 98 POINT!!!!

Simplify (23)–2

A. -1/64
B. 1/64
C. 2
D. 64

User Joel James
by
5.2k points

2 Answers

3 votes

(2 ^3)^-2

= 2^-6

= 1 / 2^6

= 1/64 answer

User Ando
by
6.3k points
2 votes

Answer:


\sf \: b) \: (1)/(64)

Explanation:

Given problem,

→ (23) - 2

Rectifying error in the problem,


\sf \rightarrow \: ( {2}^(3) ){}^( - 2)

Let's solve the problem,


\sf \rightarrow \: ( {2}^(3) ) {}^( - 2)


\sf \rightarrow \: {2}^((3 * - 2))


\sf \rightarrow \: {(2)}^( - 6)


\sf \rightarrow \: \frac{1}{ {(2)}^(6) }


\sf \rightarrow \: (1)/(64)

Hence, option (b) is correct.

User Rik Schoonbeek
by
5.9k points